The Integrating Music Into Efl Classrooms: Effects On Vocabulary Acquisition, Listening Comprehension, And Affective Factors Among Indonesian Secondary School Students - Naya Alfasha Naya (Journal of English Teaching and Linguistic Issues (JETLI), 2026)
This study examines the role of music, particularly English-language songs, in supporting English as a Foreign Language (EFL) acquisition among Indonesian secondary school students. Although interest in music-based pedagogy has increased, empirical evidence from Southeast Asian EFL contexts, especially at the secondary level, remains limited. Using a mixed-methods design, data were collected from 25 high school students through Likert-scale questionnaires, semi-structured interviews, and focus group discussions. Quantitative data were analysed using descriptive statistics to identify patterns in perceived language development, while qualitative data were thematically analysed to explore learners’ experiences and motivation. The findings show that music-based activities enhanced vocabulary retention, listening comprehension, and oral fluency, while reducing foreign language anxiety. In addition, affective dimensions of music, including emotional engagement and cultural relevance, supported sustained learner involvement. However, challenges were identified, including inappropriate song selection, linguistic complexity, and potential distraction. The study concludes that music is most effective when used as a supplementary pedagogical tool within a structured and blended instructional framework rather than as a standalone strategy for practice.